2018
DOI: 10.1111/nhs.12407
|View full text |Cite
|
Sign up to set email alerts
|

Centrality of spirituality/religion in the culture of palliative care service in Indonesia: An ethnographic study

Abstract: Experiencing life-threatening illness could impact on an individual's spirituality or religious beliefs. In this paper, we report on a study which explored cultural elements that influence the provision of palliative care for people with cancer. A contemporary ethnographic approach was adopted. Observations and interviews were undertaken over 3 months with 48 participants, including palliative care staff, patients, and their families. An ethnographic data analysis framework was adopted to assist in the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 37 publications
3
47
0
10
Order By: Relevance
“…45,49,52 Religion has a central role in everyday life for many Indonesian people. 8 Our study revealed that caregivers pray more intensively and more frequently than they did before, which confirms previous findings that religion and spirituality are used as a coping mechanism. 8,47,48 In fact, those who use positive religious coping reported higher caregiver satisfaction than those who did not use such coping.…”
Section: Discussionsupporting
confidence: 90%
“…45,49,52 Religion has a central role in everyday life for many Indonesian people. 8 Our study revealed that caregivers pray more intensively and more frequently than they did before, which confirms previous findings that religion and spirituality are used as a coping mechanism. 8,47,48 In fact, those who use positive religious coping reported higher caregiver satisfaction than those who did not use such coping.…”
Section: Discussionsupporting
confidence: 90%
“…As discussed, family caregivers also reported an underpinning moral duty to provide care due to the fear of living with guilt if the patient died due to their neglect 11,53 or the patient committing suicide due to self-stigma. 53 Reciprocity of care and what this means to the caregivers' sense of giving back to their loved ones are highlighted in other studies, 10,51,54 and this is underpinned by a strong cultural/religious belief 55 as is the idea that family caregivers must be supported. 56 Pain management is a dominant feature of palliative care, 57 and this is particularly complex in resource-poor settings where access to morphine is problematic.…”
Section: Discussionmentioning
confidence: 97%
“…This is proven in another study where it was found out that basically people lack specific information and treatment about the condition (21). Surprisingly most patients were contrary to their caregivers they think probably medical treatment could be of more relief or alternatively spiritual consecration that is believing and trusting the almighty God though prayers and being laid of hands upon them by the spiritual elders of which they could be church leaders (20).…”
Section: Perceived Causesmentioning
confidence: 96%
“…Aging appeared to be more common for both patients and caregivers and this is true because they see it is common in elderly people. However, they do not know at which age does it normally happen and also distinguish between what is normal forgetfulness and the abnormal one or the extent to which someone is termed to have a disease (16)(17)(18)(19) while others attribute it to witchcraft and this could explain why most of caregivers and patients do not take the disease to be a medical condition and instead they seek other ways of care like spiritual healing and traditional care (17,19,20) Perceived Treatment…”
Section: Perceived Causesmentioning
confidence: 99%